The modifier effects of chymotrypsin and trypsin enzymes on fluorescence lifetime distribution of N-(1-pyrenyl)maleimide-bovine serum albumin complex - Ozyigit, Ibrahim Ethem; Karakus, Emine; Pekcan, Onder (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Chymotrypsin and trypsin are the well known proteolytic enzymes, both of which are synthesized in the pancreas as their precursors the inactive forms; chymotrypsinogen and trypsinogen and then are released into the duodenum to cut proteins into smaller peptides. In this paper, the effects of activities of chymotrypsin and trypsin enzymes on fluorescence lifetime distributions of the substrat bovine serum albumin (BSA) modified with N-(1-pyrenyl)maleimide (PM) were examined. In the labeling study of BSA with PM, it is aimed to attach PM to the single free thiol (Cys34) and to all the free amine groups in accessible positions in order to produce excimers of pyrene planes of the possible highest amount to form the lifetime distributions in the widest range, that may show specifically distinguishing changes resulting from the activities of the proteases. The time resolved spectrofluorometer was used to monitor fluorescence decays, which were analyzed by using the exponential series method (ESM) to obtain the changes of lifetime distributions. After the exposure of the synthesized substrat PM-BSA to the enzymes, the fluorescence lifetime distributions exhibited different structures which were attributed to the different activities of the proteases. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fluorescence lifetime distribution; N-(1-pyrenyl)maleimide; Excimer; Bovine serum albumin; Chymotrypsin; Trypsin; ACETYLCHOLINE-RECEPTOR; PYRENE; PARTICLES; RECOVERY; MEDIA; Spectroscopy